2017
DOI: 10.1080/02656736.2017.1383517
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia treatment planning guided applicator selection for sub-superficial head and neck tumors heating

Abstract: Purpose: In this study, we investigated the differences in hyperthermia treatment (HT) quality between treatments applied with different hyperthermia systems for sub-superficial tumours in the head and neck (H&N) region. Materials and methods: In 24 patients, with a clinical target volume (CTV) extending up to 6 cm from the surface, we retrospectively analysed the predicted HT quality achievable by two planar applicator arrays or one phased-array hyperthermia system. Hereto, we calculated and compared the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…[103][104][105][106][107]113,114,116 These actions, coupled with the technological advancements in HT delivery, planning, online thermometry, and adaptive temperature modulation, should encourage integration of HT with RT and/or CT not only in LACC but also in other sites. 105,[108][109][110][111][112][117][118][119][120][121]129 It is noteworthy that 3 modal-itiesdHTRT, HTCTRT, and CTRT(3wkly Pt)dmaintained their superiority in terms of safety and efficacy in LACC, even after the sensitivity analysis for all trials published during or after 2004. The outcomes of the 2 ongoing multicentric-randomized trials in LACCdnamely, OUTBACK 130 and INTERLACE 131 daddressing NACT þ CTRT(wkly Pt) versus CTRT(wkly Pt) and CTRT(wkly Pt) þ ACT versus CTRT(wkly Pt), respectively, would be of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[103][104][105][106][107]113,114,116 These actions, coupled with the technological advancements in HT delivery, planning, online thermometry, and adaptive temperature modulation, should encourage integration of HT with RT and/or CT not only in LACC but also in other sites. 105,[108][109][110][111][112][117][118][119][120][121]129 It is noteworthy that 3 modal-itiesdHTRT, HTCTRT, and CTRT(3wkly Pt)dmaintained their superiority in terms of safety and efficacy in LACC, even after the sensitivity analysis for all trials published during or after 2004. The outcomes of the 2 ongoing multicentric-randomized trials in LACCdnamely, OUTBACK 130 and INTERLACE 131 daddressing NACT þ CTRT(wkly Pt) versus CTRT(wkly Pt) and CTRT(wkly Pt) þ ACT versus CTRT(wkly Pt), respectively, would be of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…The technological advances in hardware and software over the last decade have led to safer locoregional HT delivery, thermal treatment planning, thermal dose monitoring through noninvasive thermometry, and online adaptive temperature modulation. 105,[117][118][119][120][121] Temperature monitoring during HT in cervix cancer and the adjacent normal organs of bladder and rectum can be performed effectively through noninvasive temperature sensors. Effectiveness of HTRT over RT was also reported in an earlier pairwise meta-analysis in LACC.…”
Section: Discussionmentioning
confidence: 99%
“…This promotes the performance by (i) affording a compact size of the antenna building block, (ii) enhancing EMF coupling to the subject, and (iii) enabling broadband characteristics of the antenna. Additionally, flowing water within the bolus could be used to allow for superficial cooling during thermal interventions . Without proper impedance matching by the water bolus, the reflection coefficient showed a single self‐resonance at ~ 645 MHz.…”
Section: Discussionmentioning
confidence: 99%
“…extending up to 6 cm from the surface, can be treated using standard superficial Lucite cone or current sheet applicators, but also with the HYPERcollar, a dedicated phased-array system for head and neck tumours. Treatment planning can be used to predict treatment efficacy and a simulation study in 24 patients retrospectively analysed the predicted treatment quality achievable by the different applicators [61]. This analysis showed that in general a better target coverage is achieved with the HYPERcollar.…”
Section: A Applicator Selectionmentioning
confidence: 99%
“…This analysis showed that in general a better target coverage is achieved with the HYPERcollar. However, adequate target coverage can also be achieved with a Lucite cone applicator for tumours extending up to 5 cm from the patient surface, provided that the aperture fully covers the target [61].…”
Section: A Applicator Selectionmentioning
confidence: 99%